Correlation Between Electrocochleographic Changes During Surgery and Hearing Outcome in Cochlear Implant Recipients: A Case Report and Systematic Review of the Literature. Issue 3 (March 2020) - Dalbert, Adrian; Rohner, Peter; Roosli, Christof; Veraguth, Dorothe; Huber, Alexander; Pfiffner, Flurin
Abstract : Objective: To determine the correlation between intraoperative changes of electrocochleography (ECochG) responses and traumatic cochlear implant insertions as well as postoperative hearing loss. Methods: ECochG, radiological, and audiological data were collected prospectively in a cochlear implant recipient with otosclerosis and assumed cochlear trauma during electrode insertion. A systematic review was conducted within PubMed-NCBI, EMBASE, and the Cochrane Library using the terms "Cochlear implant" and "Electrocochleography." Original studies that evaluated intraoperative ECochG responses and postoperative hearing loss were selected and analyzed. Results: The case report revealed a drop of intra- and extracochlear ECochG signals during electrode insertion. The postoperative computed tomography scan suggested a scalar dislocation. There was no measurable hearing 4 weeks after surgery. Within the database search, nine articles met the inclusion criteria. All were case series reports (range from 2 to 36 subjects) with a total of 173 subjects. Due to the heterogeneous data, a meta-analysis was unfeasible. Conclusions: In concordance with some findings in the literature, the presented case report suggests that a drop of intra- and extracochlear ECochG signals during the insertion of the electrode array is associated with cochlear trauma and postoperative hearing loss in some cases. However, the literature is inconclusive regarding the correlation between intraoperative changes of the ECochG signals and postoperative hearing preservation. More studies investigating the correlation are needed to provide sufficient data. Abstract : Supplemental Digital Content is available in the text